IMPLEMENTATION OF A COSTING SYSTEM IN THE ESPOCH, FROM THE OPTIC OF SOCIAL PROBLEMS OF SCIENCE - Brito Garzón, Mónica; Escobar Vargas, Iván; Andrade Martinez, Ana (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019DO - 10.36779/mktdescubre/v#.#, 2020)
The university was born as an essentially universal institution, a quality that yields to the pressures of nationalist interests. However, universities are the main social spaces for the creation and dissemination of knowledge, whose transformative potential can contribute to the social and human development of their local environments. At the end of the 20th century, the social function of the university acquires particular features, as a consequence of the growing scientific, social and economic changes associated with the global phenomenon. Today, Higher Education institutions operate in a globalized environment, whose needs and demands transcend local, national and regional visions, reaching global dimensions. In the current scheme of world relations dominated by competition and the deepening of gaps and asymmetries, the role of higher education has been resized as a transformative space for social dynamics in developing countries. For universities, this implies recovering their original universal vision, based on a cultural change that allows them to redesign their academic and management processes in order to increase their quality, relevance and impact. In the current complex and changing context, for the Latin American university, recovering its universal character and developing the skills that guarantee excellence and relevance is a major challenge.